BIOTECHNOLOGICAL APPROACHES TO THE CREATION OF NEW FERMENTED DAIRY PRODUCTS - Nadirova , S.; Sinyavskiy , Yu. (Eurasian Journal of Applied Biotechnology, 2023)
The industrial production of balanced and healthy food has always been one of the most important tasks facing humanity. To solve this problem, research is relevant in the field of creating functional milk-based synbiotic products, which, along with traditional lactic acid microorganisms, include strains of probiotic bacteria with a proven specific positive effect on the macroorganism, and prebiotic substances that increase the selectivity of the benefits of the "useful" microflora of the gastrointestinal tract-intestinal tract and its biological activity.Along with lactic acid bacteria used as starters in fermented milk products, there is a population of predominantly adventitious heterofermentative lactobacilli that can have a positive effect on dairy products.This article describes the use of facultatively and obligately heterofermentative species such as Lactobacillus bulgaricus, Streptococcus thermophilus and Lactobacillus fermentum 14. The general characteristics of these species are described, as well as the desired properties (probiotic activity and taste formation) that affect the characteristics of dairy products.The general characteristics of these species are described along with the desired (probiotic activity and taste formation) properties affecting the characteristics of dairy products.Samples of yogurt based on probiotic starter cultures enriched with plant fillers were studied. The technological process of production was carried out in the traditional way. The dynamics of acid accumulation was studied, titratable and active acidity were determined. As a result of the study, it was revealed that the combination of fermented milk products with plant fillers slightly accelerates the fermentation process.